Developing capacity for innovation in complex systems : strategy, organisation and leadership - Vindeløv-Lidzélius, Christer (Routledge studies in innovation, organization and technology., 2021)
"Based on a theoretical analysis and supported by both explorative qualitative and quantitative research, this book examines the many reasons why an initiative becomes an innovation and why some organizations are better at innovation than others. Developing Capacity for Innovation in Complex Systems offers insights into the history of the idea of innovation, as well as knowledge around different discourses on innovation. The purpose of this book is to help organisations further their aspirations and work with innovation. It is based on two premises: 1) that capacity can be developed, 2) that it is worthwhile trying to do so, and 3) there are however no guarantees for success. Providing a comprehensive view of innovation and discussing the theoretical challenges, the book contributes towards a holistic theory for capacity building for innovation. The book conveys frameworks, methodologies and tools that are used in terms of innovation, and it explains positive strategies for innovation that are being developed. Complexity theory is presented and attributed to the construct of innovation to further the understanding of the intricacies and fallacies of innovation work. This book will be of direct interest to scholars and subject matter experts in the field of innovation management. Business leaders and reflective practitioners will find the content relevant and accessible"--